TRANSFORMATION OF ISLAMIC EDUCATION IN ADDRESSING THE CHALLENGES OF A MULTICULTURAL SOCIETY - Rafid, Reni Haryani; Darmawati (EDUCATUM: Scientific Journal of Education, 2025)
Islamic education plays a strategic role in shaping religious identity while responding to the challenges of increasingly multicultural societies. In plural contexts such as Indonesia, Islamic educational institutions are required to move beyond normative and text-centered approaches toward more inclusive, contextual, and socially responsive educational practices. This study aims to explore how Islamic education is transformed to address the realities of multicultural society and to examine the challenges encountered in this process. Employing a qualitative research design with an interpretive approach, data were collected through in-depth interviews, observations, and document analysis involving teachers, institutional leaders, and students from selected Islamic schools and pesantren. Data were analyzed using thematic analysis to identify key patterns related to educational transformation, multicultural values, and institutional practices. The findings reveal that the transformation of Islamic education is characterized by a paradigm shift toward dialogical pedagogy, contextual curriculum design, and the integration of values such as tolerance, inclusivity, and religious moderation. Islamic educational institutions, particularly pesantren, were found to function as agents of social cohesion by promoting intercultural dialogue and community engagement within plural environments. However, the study also identifies significant challenges, including curricular rigidity, limited teacher competence in multicultural pedagogy and digital literacy, and insufficient institutional support.This study concludes that the transformation of Islamic education is both a pedagogical necessity and a socio-religious imperative in multicultural societies. Grounded in Islamic educational principles such as ta’d?b, justice, compassion, and balance, transformative Islamic education has the potential to strengthen religious understanding while fostering social harmony. The findings contribute to the discourse on inclusive Islamic education and provide insights for curriculum development, teacher professional development, and educational leadership in multicultural contexts.